MODEL KOMUNIKASI PARIWISATA RELIGI DALAM PENGEMBANGAN WISATA KABUPATEN ROKAN HULU - Ismandianto Ismandianto; Belli Nasution; Evawani Elysa Lubis (Universitas Merdeka Malang, 2020)
Tourism is a travel activity carried out by a person or group of people to a place to meet their needs and desires. This study aims to produce a model of religious tourism communication in the Rokan Hulu Regency. This research begins describing the development of religious tourism attraction objects in Rokan Hulu, analyzing the communication strategies adopted to attract tourists to the Rokan Hulu Regency. The method applied in this study was qualitative by interviewing several informants from the MAMIC, the Rokan Hulu District Culture and Tourism Office and the Suluk community. Results of this study indicate that religious tourism in area has begun to develop quite well, integrated don’t tourism management and communication between the local government, MAMIC and the Suluk mosque which are relied upon as religious tourism objects seem to run on their own terms. Likewise, tourism communication applied is also not integrated, each of these attractions is known because of the word of mouth communication The existence of social media, radio and tv is a communication channel for these attractions so that it is widely known, magnificent buildings and rituals of worship are the main attraction of this religious tourism object.